2022
DOI: 10.3389/fevo.2022.924941
|View full text |Cite
|
Sign up to set email alerts
|

Modern approaches for leveraging biodiversity collections to understand change in plant-insect interactions

Abstract: Research on plant-pollinator interactions requires a diversity of perspectives and approaches, and documenting changing pollinator-plant interactions due to declining insect diversity and climate change is especially challenging. Natural history collections are increasingly important for such research and can provide ecological information across broad spatial and temporal scales. Here, we describe novel approaches that integrate museum specimens from insect and plant collections with field observations to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Such combinations unveil the potential for insight into the nature of species interactions over time that will lead to a more comprehensive understanding of historical community structures, trophic dynamics, extinction dynamics, and the importance of functional diversity for ecosystem resilience. With the convergence of accessible and broader‐scale data sets from various collections, researchers can investigate historical species interactions, such as predator–prey relationships and mutualistic associations, competition among native and invasive species (Bodt et al., 2020), and other coevolutionary relationships between species that occur over extended periods (Balmaki et al., 2022).…”
Section: Characteristic Examplementioning
confidence: 99%
“…Such combinations unveil the potential for insight into the nature of species interactions over time that will lead to a more comprehensive understanding of historical community structures, trophic dynamics, extinction dynamics, and the importance of functional diversity for ecosystem resilience. With the convergence of accessible and broader‐scale data sets from various collections, researchers can investigate historical species interactions, such as predator–prey relationships and mutualistic associations, competition among native and invasive species (Bodt et al., 2020), and other coevolutionary relationships between species that occur over extended periods (Balmaki et al., 2022).…”
Section: Characteristic Examplementioning
confidence: 99%
“…Theiss et al (2007) reported that wasps effectively pollinated some milkweed ( Asclepias ) species, even as butterflies were ineffective. Butterflies are frequently invoked as pollinators (e.g., Balmaki et al, 2022; Tan et al, 2023) but often carry very little pollen (Larson et al, 2018). Beetles are recognized as important pollinators in tropical regions but have received less attention in temperate latitudes (Bernhardt, 2000; Sayers et al, 2019).…”
Section: Introductionmentioning
confidence: 99%